Environment and Natural Resources Management: Lessons from City Program Innovations - Ruben G. Mercado (Philippine Institute for Development Studies (PIDS), 1998)
The enactment of 1991 Local Government Code has brought greater responsibilities for local government units to manage their natural resources and the environment. This move has encouraged greater dynamism and innovation in some Philippine cities. Strategies employed and programs undertaken by various cities largely depend on the stage of development and their respective focus and priorities. For large urban cities, environmental problems are associated with growth and economic activity and thus, a special attention is given for a clean air and a healthy environment. This paper aims to draw lessons from selected cities that have undertaken innovative environmental programs and to highlight key elements that have made their programs successful and sustainable.
Keywords: 330; metropolitan structure; metropolitan planning and development; environmental management